PP-7 CHILDHOOD RECURRENT ABDOMINAL PAIN IS ASSOCIATED WITH DUODENAL EOSINOPHILIA REGARDLESS OF H. PYLORI INFECTION. Issue 4 (October 2015) - Wauters, L.; Harris, P.; Serrano, C.; Villagrán, A.; Duarte, I.; Rakhra, G.; Jones, M.; Talley, N.; Crabtree, J.; Walker, M.
<x xml:space="preserve">Abstract</x> Objectives: This study aimed to investigate histologic features of children with RAP undergoing upper gastrointestinal endoscopy, after exclusion of common organic disease. Methods: Children referred for endoscopy were prospectively enrolled at a single tertiary center between 2008 and 2010, after obtaining informed consent. Cases were defined as children with clinical diagnosis of RAP, as opposed to controls with suspicion of organic disease. Gastric and duodenal biopsies were analysed by pathologists blinded to indication. Demographic and clinical variables, H. pylori infection, biochemical, endoscopic and pathologic results were compared between cases and controls. Results: A total of 101 children were included after exclusion of villous enteropathy (n = 6) and parasitic, rotaviral or salmonella enteritis (n = 14), resulting in 72 cases and 29 controls. There were no significant differences in demographics, clinical symptoms, H. pylori infection and endoscopic findings between cases and controls. Duodenal eosinophil counts per 5 HPF were significantly increased in cases vs. controls (median (IQR) 86 (62–114) vs. 49 (31–88); p < 0.001) and did not differ regarding age, gender and H. pylori. Intraepithelial lymphocytes per 100 enterocytes were similar in cases vs. controls (19 (15–25) vs. 18 (14–23); p = 0.89) with ≥ 25 in 25% of cases. Duodenal eosinophilia was equally observed in H. pylori negative cases (n = 50) vs. controls (n = 19) (87 (61–119) vs. 53 (36–95); p = 0.01), as well as positive cases (n = 21) vs. controls (n = 10) (85 (55–105) vs. 42 (18–65); p = 0.03). Logistic regression yielded an adjusted odds ratio of 1.23 (95% CI 1.08–1.40) for duodenal eosinophilia in RAP. Conclusions: Children with a clinical diagnosis of RAP have marked duodenal eosinophilia, independent of H. pylori infection, suggesting the role of unknown infectious or allergic triggers in the pathogenesis of functional gastrointestinal disorders in childhood. Further research is needed on the diagnostic and therapeutic benefits of targeting duodenal eosinophilia.